2002
DOI: 10.1046/j.1365-2036.2002.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ‘nutriceutical’, bovine colostrum, for the treatment of distal colitis: results from an initial study

Abstract: SUMMARYBackground: Bovine colostrum is a rich source of nutrients, antibodies and growth factors. Aim: To examine the efficacy of colostrum enemas in the treatment of distal colitis using a randomized, doubleblind, controlled protocol. Methods: Fourteen patients (eight female), with a mean age of 45 years (range, 16-75 years) and mild to moderately severe distal colitis (Powell-Tuck scoring system), received colostrum enema (100 mL of 10% solution) or placebo (albumin solution) b.d. for 4 weeks. Both groups al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 16 publications
(22 reference statements)
2
61
0
Order By: Relevance
“…The use of "natural" products, such as this colostral preparation, has several potential advantages. We have previously shown that they possess greater intrinsic stability against luminal digestion than isolated individual peptides (8) and that combination therapy with peptides provides the potential for the stimulation of gut stabilization or healing in a synergistic fashion (7). Furthermore, there is currently a demand from the general public for more natural types of products, which are usually considered as "alternative therapy," but which can possess potent biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of "natural" products, such as this colostral preparation, has several potential advantages. We have previously shown that they possess greater intrinsic stability against luminal digestion than isolated individual peptides (8) and that combination therapy with peptides provides the potential for the stimulation of gut stabilization or healing in a synergistic fashion (7). Furthermore, there is currently a demand from the general public for more natural types of products, which are usually considered as "alternative therapy," but which can possess potent biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…In other species bovine colostrum has been demonstrated to improve gut restoration. Giving orally, bovine colostrum prevents chemically-induced villous atrophy in mice (Playford et al, 1999) and stimulates mucosal healing of patients suffering from inflammatory gut disease (Khan et al, 2002). Our studies aim at evaluating effects of bovine colostrum on gut restoration in weaned piglets.…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects could be explained by both an observed increase in feed intake level as early as the first days after weaning [1] and a likely direct effect on gut health. Giving bovine colostrum orally prevents chemically-induced villous atrophy in mice [3] and stimulates mucosal healing of patients suffering from inflammatory gut disease [4]. It reduces diarrhoeal symptoms in infants [5] and protects intestinal mucosa from pathogen bacteria adhesion [6].…”
Section: Introductionmentioning
confidence: 99%